Works councils and apprenticeship training : heterogeneous works councils, heterogeneous effects? - Weis, Kathrin [Verfasser]; Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2025)
"In Germany, works councils possess co-determination rights concerning apprenticeship training, which may influence training outcomes in firms. While the literature commonly assumes homogeneous effects of works councils, this study reveals considerable heterogeneity in their involvement in training-related decisions. Using representative German firm-level data, we explore two dimensions of works councils’ heterogeneity: their participation in various apprenticeship-related decisions and their overall perceived success in enforcing their agendas. We document how these dimensions of works council heterogeneity are associated with firms’ decisions on whether to train apprentices, the intensity of training (the number of apprentices relative to total employment) and apprentice retention and dropout rates. Our findings indicate that works council participation is associated with higher training propensity and higher apprentice retention rates, but it has no significant link to training intensity. Interestingly, works councils rated as successful are associated with lower apprentice dropout rates but also lower retention rates for graduates, highlighting a trade-off between ensuring training quality and navigating the potentially conflicting interests of apprentices and incumbent workers.” (Authors’ abstract; BIBB-Doku)
Der Artikel wurde nach der online-first-Veröffentlichung folgendem Heft zugeordnet: 64 (2026), H. 2, Seite 250-262
Keywords: S 3.5.4 Sozialpartner; S 3.2 Unternehmen und Behörden; 370; Betrieb; Betriebsrat; Mitbestimmung; Einflussfaktor; Ausbildungsverhalten; Berufsausbildung; Ausbildungsabbruch